2014
DOI: 10.2105/ajph.2013.301669
|View full text |Cite
|
Sign up to set email alerts
|

An Increasing Socioeconomic Gap in Childhood Overweight and Obesity in China

Abstract: We used a new conceptual framework that integrates tenets from health economics, social epidemiology, and health behavior to analyze the impact of socioeconomic forces on the temporal changes in the socioeconomic status (SES) gap in childhood overweight and obesity in China. In data from the China Health and Nutrition Survey for 1991 to 2006, we found increased prevalence of childhood overweight and obesity across all SES groups, but a greater increase among higher-SES children, especially after 1997, when inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 52 publications
3
50
1
Order By: Relevance
“…Due to mixed development in these middleincome countries, and China in particular, it is difficult to Electronic supplementary material The online version of this article (https://doi.org/10.1007/s12529-017-9688-6) contains supplementary material, which is available to authorized users. establish exactly where Chinese children fit along the nutrition transition spectrum [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to mixed development in these middleincome countries, and China in particular, it is difficult to Electronic supplementary material The online version of this article (https://doi.org/10.1007/s12529-017-9688-6) contains supplementary material, which is available to authorized users. establish exactly where Chinese children fit along the nutrition transition spectrum [11].…”
Section: Introductionmentioning
confidence: 99%
“…Rural areas of the country have lower incomes than urban areas-particularly as compared to Shanghai-with less variation in SES. Evidence also suggests that childhood overweight/obesity has increased more rapidly among high-SES families than low-SES families between 1991 and 2006, particularly in urban areas [11], yet little is known about the factors associated with SES differences in overweight and obesity among children in China today.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity have remarkably increased in children and adolescents, especially among socially excluded populations (9). He et al (2014) showed that family socioeconomic status (SES) is associated with overweight and obesity in childhood and adolescence. However, this might represent a conditional relationship which is dependent on the country's stage of Copyright development (10).…”
Section: Introductionmentioning
confidence: 99%
“…He et al (2014) showed that family socioeconomic status (SES) is associated with overweight and obesity in childhood and adolescence. However, this might represent a conditional relationship which is dependent on the country's stage of Copyright development (10). In developed countries, obesity is more common in individuals with low SES than in people with high SES (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation